Review of Antihypertensive Activity of Purslane (Portulaca oleracea L.) - Azizah, Rizqi Nur; Putra, Bayu; Suhaenah, Asriani; Saputri, Fadlina Chany; Ahmad, Aktsar Roskiana; Malik, Abdul (Journal of Pharmaceuticals and Natural Sciences, 2025)
Hypertension is a chronic disease in which blood pressure in the arteries increases. Hypertension is a health problem that has a risk of causing other diseases such as coronary heart disease, kidney failure, nerve dysfunction and stroke. Plants such as purslane (Portulaca oleracea L.) are one of the plants that have benefits in treating disease. The purpose of the review article is to determine the potential of Portulaca oleracea L. as an anti-hypertensive. This research is a Review Journal. The subject of this review is national and international articles indexed nationally and internationally in the last 10 years which discuss the antihypertensive ability of Portulaca oleracea L. by classifying them based on the type of study and test model used in-vivo, the potential of the plant in lowering blood pressure, mechanism of action in treating hypertension, and specific chemical constituents responsible for anti-hypertensive activity. Based on the results of studies conducted on several journal articles, it can be concluded that Portulaca oleracea L. : 1. exhibits promising antihypertensive properties through various mechanisms, including vasodilation, reduction of heart rate, and improvement of endothelial function; 2. Clinical trials and comparative studies indicate that it can significantly reduce systolic blood pressure, making it a potential natural adjunct in managing hypertension; 3. exhibits multiple mechanisms that can help manage hypertension, primarily through its antioxidant, anti-inflammatory, and lipid-regulating properties, 4. contains several bioactive compounds that contribute to its antihypertensive effects such as Asperglaucide (ASP), Oleracein E and Oleracein L, Omega-3 Fatty Acids, Quercetin, and Rutin.